2018
DOI: 10.1590/fst.16017
|View full text |Cite
|
Sign up to set email alerts
|

Technologies applied to sorghum (Sorghum bicolor L. Moench): changes in phenolic compounds and antioxidant capacity

Abstract: The search for foods with biological potential for the prevention of chronic diseases has highlighted sorghum, and numerous studies have been conducted to determine the best processing conditions without compromising the nutritional, functional or sensory qualities. We conducted a review of the scientific literature on the techniques used in sorghum and their effects on phenolic compounds and antioxidant capacity. This review allowed us to conclude that the type and content of phenolic compounds in the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 84 publications
(132 reference statements)
0
23
0
1
Order By: Relevance
“…On the other hand, a direct correlation between GABA and CA ( r = 0.5029), and pCA ( r = 0.6242) was found. In this sense, phenolic acids and GABA are secondary metabolites which act in stress conditions in plants (Boonstra et al, ; Salazar‐López, González‐Aguilar, Rouzaud‐Sández, & Robles‐Sánchez, ). Thus, sorghum hybrids could produce different secondary metabolites and have diverse response to stress during germination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a direct correlation between GABA and CA ( r = 0.5029), and pCA ( r = 0.6242) was found. In this sense, phenolic acids and GABA are secondary metabolites which act in stress conditions in plants (Boonstra et al, ; Salazar‐López, González‐Aguilar, Rouzaud‐Sández, & Robles‐Sánchez, ). Thus, sorghum hybrids could produce different secondary metabolites and have diverse response to stress during germination.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a direct correlation between GABA and CA (r = 0.5029), and pCA (r = 0.6242) was found. In this sense, phenolic acids and GABA are secondary metabolites which act in stress conditions in plants (Boonstra et al, 2015;Salazar-López, González-Aguilar, Rouzaud-Sández, & Robles-Sánchez, 2018 there is an indirect correlation with color. Dicko et al (2005) reported that after germination of sorghum varieties, the correlation between antioxidant activity and phenolics was weaker than that for native grains, due to during germination there is a synthesis of other antioxidant compounds like vitamin C, antioxidant peptides, and free amino acids.…”
Section: Bio-functional Propertiesmentioning
confidence: 99%
“…65 Three poorly known compounds were identified in the present work: 1-O-dihydrocaffeoylglycerol (m/z 255), 1,3-O-dicaffeoyglycerol (m/z 415) and 1,3-O-caffeoyldihydrocaffeoylglycerol (m/z 417), all of which belong to the class of the phenylpropane glycerides, which are glycerol esters of phenolic acids. These compounds were mentioned as being one of the sources of phenolic acids in sorghum grains in the work of Salazar-Lopez et al, 46 and identified in the studies of Kang et al 63 and Wu et al 66 with sorghum grains.…”
Section: (−)Ps-ms Fingerprintsmentioning
confidence: 98%
“…This may be related to the presence of tannin in this variety and to the fact that most of the phenolic compounds are present in the outer layers of the grain, such as the pigmented forehead, this region being only present in SC 319. 46…”
Section: Ps-ms Chemical Profilementioning
confidence: 99%
“…Various pretreatment technologies have been developed to reduce polyphenols content in cereals. Salazar‐Lopez, Gonzalez‐Aguilar, Rouzaud‐Sandez, and Robles‐Sanchez () reported on the most recent techniques used in sorghum and their phenolic compounds and antioxidant capacity. Some of these methods include mechanical procedures such as milling, decortication, and extrusion; physical methods, for example steaming, radiation, and sonication; biological methods or bioprocessing such as microbial and enzymatic degradation.…”
Section: Introductionmentioning
confidence: 99%